Теремок: [сказка] / [художники - Р. Кобзарев, О. Савина] - Кобзарев Роман Иванович (Серия "Русские сказки", 2015)
Экземпляры: ф.16 (20160516) / Инвентарный номер: 47826 / Цена: 20.00 / Сис.шифр: Д / Авт.знак: Т 35 / ГРНТИ: 17.71 / ББК: 82.3(2)